Vehicle-based cryogenic rail cleaning: an alternative solution to 'leaves on the line'. Issue 4 (23rd August 2021) - Krier, Peter; White, Ben T; Ferriday, Paul; Watson, Mike; Buckley-Johnstone, Luke; Lewis, Roger; Lanigan, Joseph L
Abstract : Contamination of rail lines with leaves and other organic matter and oxides can affect the traction of train wheels and cause safety issues, delays and schedule changes. The main solution in the UK is to use specialist rail-head-treatment trains that clean rails with high-pressure water jets. But these trains cannot cover all UK mainline infrastructure due to limited availability and gauging issues. As such, there is a need for a rapid-response mobile solution to expand this capability. This paper reports on successful field trials of a small road-to-rail vehicle fitted with dry-ice blasting equipment, and the effect this has on both cleaning rails and improving train braking.